Cytological Diagnosis Of Nodular Hidradenoma - A Case Report - DR.MAMATHA K,; DR. ARAKERI S U,; DR.NITASHA DHAWAN, (International Journal of Pharma and Bio Sciences, 2015)
Nodular hidradenoma is a benign adnexal tumor. Its origin is either from eccrine or apocrine structures. Fine needle aspiration cytology (FNAC) of skin lesions is not widely practiced and there is a lack of adequate cytological diagnostic criteria for various skin lesions.Cytomorphological features of nodular hidradenoma are rarely reported in the literature. Most of the cases are misinterpreted on cytology or sometimes remain inconclusive. Skin adnexal tumours are not routinely subjected for FNAC. Hence an awareness of cytological features of these lesions is important to prevent misdiagnosis and over treatment. We present here a case of nodular hidradenoma diagnosed on cytology in a 37 year old female.